Investigation of emissions of rare earth ions and ZnO nanocrystals embedded in SiO2 film - Harvind s/o Sekhar (Nanyang Technological University, 2024)
Optics has increasingly been playing a crucial role in solid state physics in recent times. The inclusion of Rare Earth ions has vastly improved the versatility of optical instrument’s applications. For example, creating highly sensitive photos, white light diodes and many other devices. This project is a continuation of a previous study published by Kantisara Pita and Vivek Mangalam titled – White light emission from thin-film samples of ZnO nanocrystals, Eu3+ and Tb3+ ions embedded in an SiO2 film. In this study, emissions at 614nm and 545nm from Eu3+ and Tb3+ ions, respectively, is due to the energy transfer from the excited ZnO nanocrystal to the Rare Earth ions. This only requires the single excitation wavelength in the sample to produce a desired colour. Through the works, based on a 4th degree polynomial equation, the concentration of Eu3+ and Tb3+ ions for a white light emitting sample were found to be at 0.012 and 0.024 molar fractions, respectively. The purpose of the previous study was to develop an energy efficient solid state lighting device. This is important because the aim was to fabricate a device that uses low-cost-sol-gel process. To do this, the two general methods used for displays, general lighting and automobile headlights being, phosphor conversion ion in which a UV blue light emitting diode is used along a yellow phosphor and a combination of red, blue, and green LEDs were combined to produce white light.